2007
DOI: 10.1136/gut.2007.125690
|View full text |Cite
|
Sign up to set email alerts
|

Rectal compliance and rectal sensation in constipated adolescents, recovered adolescents and healthy volunteers

Abstract: While rectal compliance in RC subjects is lower when compared with adolescents with FC, almost half of the RC subjects showed an increased rectal compliance. The role of rectal compliance in therapy-resistant FC seems limited, because recovery is possible despite an increased rectal compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…We found that the decompressed colon often demonstrates improved contractility in postoperative motility studies. Moreover, sustained evacuation of the rectal vault seems to permit it to reset its resting volume, although studies by van den Berg et al [6] suggest that it never reaches the size of normal volunteers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that the decompressed colon often demonstrates improved contractility in postoperative motility studies. Moreover, sustained evacuation of the rectal vault seems to permit it to reset its resting volume, although studies by van den Berg et al [6] suggest that it never reaches the size of normal volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 6 subjects with an unsatisfactory outcome owing to persistent constipation, 4 underwent a subsequent surgical procedure after an average of 13 months: 2 had colonic resections with primary reanastomosis, and 2 underwent diversion. The average age of children achieving satisfactory results after ACE was 8 years (range, [3][4][5][6][7][8][9][10][11][12][13][14], whereas the average age of children with unsatisfactory results was 12 years (range, 5-17) (P = .08), suggesting a trend but not achieving statistical significance. Lack of cooperation among teenage patients in administering the enemas was identified by caregivers as sometimes contributing to ACE failure.…”
Section: Ace Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the clinical importance of impaired peripheral sensations in children has been questioned [30]. Although earlier studies reported that larger rectal distension volumes were needed to trigger rectal sensation in constipated children [227,228], more recent studies found no difference in sensory function in children with functional constipation when compared to healthy volunteers [229,230], although rectal compliance (stretch response to an imposed force) was greater (i.e. the rectum was more lax) in constipated individuals.…”
Section: Rectal Sensorimotor Activitymentioning
confidence: 97%
“…Later it was clearly recognized in individuals with idiopathic constipation 11,12. More recent work has shown that blunted sensation to rectal distension occurs in almost a quarter of adult patients with chronic idiopathic constipation,11-13 and in up to two-thirds of idiopathic pediatric constipation 14-16. It is also found in 10% of patients with fecal incontinence 17.…”
Section: Introductionmentioning
confidence: 98%